Effect of Feeding on Juvenile Growth Rate of Wader Fish (Rashbora argyrotaenia) - Dewi, Ravita Kusuma; Arthana, I Wayan; Pebriani, Dewa Ayu Angga (Advances in Tropical Biodiversity and Environmental Sciences; Vol 5 No 3 (2021): ATBESDO - 10.24843/ATBES.2021.v05.i03.p01, 2021)
Aquaculture is an activity to develop, obtain, reproduce and produce a fishery with the help of human resources. One of the cultivation practices is wader fish ( Rashbora argyrotaenia ) which is known for its very slow growth and relatively small size. This study aims to determine the growth rate of wader fish with different feeds in Blado Kulon Village, Tegalsiwalan, Probolinggo. The feed used was feed A in the form of fish pellets as a control, feed B consisting of a mixture of conch flour, soybean flour, bran, and tapioca flour, while feed C consisted of a mixture of conch flour, cassava leaf flour, bran and tapioca flour. The study was conducted for 42 days. The parameters measured in this study were temperature, DO, and pH, as well as observing the growth in absolute weight, specific growth rate (SGR), survival rate, and feed concentration ratio (FCR). Observations were analyzed using One Way Analysis of Variance (ANOVA) and further tests were carried out using the Duncan test. The results showed that different feeding did not have a significant effect on growth rate, absolute weight, feed conversion ratio, and survival of wader fish. Water quality parameters measured include temperature with an average of 28.42oC - 28.54 oC, while pH has an average of 7.42 - 7.50, and dissolved oxygen (DO) with an average of 5.54 - 6, 23 mg / L.